Presence of antibiotic residues in various environmental compartments of Shandong province in eastern China: Its potential for resistance development and ecological and human risk. (May 2018) - Hanna, Nada; Sun, Pan; Sun, Qiang; Li, Xuewen; Yang, Xiwei; Ji, Xiang; Zou, Huiyun; Ottoson, Jakob; Nilsson, Lennart E.; Berglund, Björn; Dyar, Oliver James; Tamhankar, Ashok J.; et al.
Abstract: Objectives: To investigate the occurrence of antibiotic residues in different types of environmental samples including water samples in rural Shandong province, China. Further, to characterize the potential ecological risk for development of antibiotic resistance in the environment, and the potential direct human health risk of exposure to antibiotics via drinking water and vegetables. Methods: Environmental samples ( n  = 214) (river water, waste water, drinking water, sediments, manure, soil and edible parts of vegetables) were collected in twelve villages in Shandong province in eastern China. High performance liquid chromatography–tandem mass spectrometry (HPLC–MS/MS) was used to determine the concentration of antibiotic residues. The ratio of the measured environmental concentrations (MEC) to the predicted no-effect concentrations (PNEC) was used to evaluate the ecological risk (risk quotient, RQ) for development of antibiotic resistance. The potential risks to human health through exposure to antibiotics in drinking water were assessed by comparing measured environmental concentrations (MEC) and predicted no-effect concentration in drinking water (PNECDW ), and in vegetables by comparing estimated daily intake (EDI) to ADI. Results: Sulfapyridine, sulfamethoxazole, ciprofloxacin, enrofloxacin, levofloxacin, norfloxacin, chloramphenicol, florfenicol, doxycycline, and metronidazole were detected at concentrations ranging between 0.3 and 3.9 ng/L in river water, 1.3 and 12.5 ng/L in waste water, 0.5 and 21.4 ng/L in drinking water, 0.31 and 1.21 μg/kg in river sediment, 0.82 and 1.91 μg/kg in pig manure, 0.1 and 11.68 μg/kg in outlet sediment, 0.5 and 2.5 μg/kg in soil, and 6.3 and 27.2 μg/kg in vegetables. The RQs for resistance development were >1 for enrofloxacin, levofloxacin, and ranged between 0.1 and 1 for ciprofloxacin. MECs/PNECDW ratios were <1 from exposure to antibiotics through drinking water for both adults and children. EDI/ADI ratios were <0.1 from exposure to antibiotics by vegetable consumption. Conclusions: Antibiotic pollutants were ubiquitous in various environmental compartments of Shandong province of China. Risk estimates indicated a potential for the measured levels of enrofloxacin, levofloxacin and ciprofloxacin in waste water to pose an ecological risk for resistance selection, and further studies are needed to validate this finding. The investigated antibiotics did not appear to pose an appreciable direct human health risk from environmental exposure through drinking water or vegetables consumption. However, they might still pose a risk for resistance development. Highlights: In Shandong province of China, antibiotic residues were present in various compartments. Fluoroquinolone in waste water posed potentially moderate and high ecological risk for development of resistance. The antibiotic did not pose a direct risk to human health, but might cause an important risk of resistance development.